Intrinsic defect formation and the effect of transition metal doping on transport properties in a ductile thermoelectric material α-Ag2S: a first-principles study. Issue 16 (16th March 2021) - Ngoc Nam, Ho; Yamada, Ryo; Okumura, Haruki; Nguyen, Tien Quang; Suzuki, Katsuhiro; Shinya, Hikari; Masago, Akira; Fukushima, Tetsuya; Sato, Kazunori
Abstract : The significant power factor enhancement of an α-Ag2 S system by up to 40% by doping Cu or Au is predicted by using the SCAN + rVV10 functional. Abstract : In this paper, the electronic structure and transport properties of a ductile thermoelectric material α-Ag2 S are examined using first-principles calculations combined with the Boltzmann transport equation within a constant relaxation-time approximation. The use of the exchange–correlation functional SCAN + rVV10 successfully describes the geometric and electronic structure of α-Ag2 S with a direct bandgap value of 0.99 eV, which is consistent with the previous experimental observations. Based on the calculations of the formation energy of typical intrinsic defects, it is found that intrinsic defect formation greatly affects the conductivity of the system where silver vacancy and interstitial silver act as p-type and n-type defects, respectively. Large Seebeck coefficients at room-temperature, of around −760 μV K −1 for n-type and 1400 μV K −1 for p-type, are realized. It is also suggested that the doping of fully filled d -block elements such as Cu and Au not only maintained the Seebeck coefficients at high values but also improved electrical conductivity by more than 1.4 times, leading to the improvement of the power factor by up to 40% compared to the non-doped sample at low carrier concentration.